Outcome Comparison of Midazolam And Succinylcholine in Laryngeal Mask Airway (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: The most vital element in providing functional respiration is the airway and the major responsibility of the anesthetist is to provide respiration for the patient through a patent airway and adequate ventilation. The use of Laryngeal Mask Airway (LMA) is well established in anesthetic practice. The LMA is an innovative airway management device intended as an alternative airway to face mask use and being used in millions of patients for routine and emergency procedures. LMA obviates the need for tracheal intubation during anesthesia. The efficacy of thiopentone can be altered by midazolam or succinylcholine in combination. We used thiopentone sodium (5mg/kg) and midazolam (0.05mg/kg) as induction agent in group A (Control group) and thiopentone sodium (5mg/kg) and succinylcholine (0.25mg/kg) in group B for LMA. This randomized trial was conducted to compare the effectiveness of midazolam and succinylcholine added with thiopentone in smooth insertion of LMA. Materials and methods: The study was done in the Department of Anesthesiology, Chittagong Medical College from July 2013 to December 2014. All the patients scheduled for elective surgical procedures under general anesthesia fulfilling the inclusion criteria, were the study population. Data was analyzed by computer based software SPSS-17. Results: Mean age of patients were 33.50 years ± SD- 10.629 years in group A and 32.22 years ± SD- 9.192 years in group B. In all patients (42) from group A, LMA was successfully inserted after first attempt and in group B 36 (85.71%) patients required single attempt. The overall insertion condition of LMA was excellent in 21 (50%) patients in group A and in 13 (30.95%) patients in group B. Conclusion: In the perspective of our study, midazolamthiopentone sodium is more effective and safe to use in smooth insertion of LMA.JCMCTA 2018 ; 29 (1) : 17-22